Infaq and Shadaqah as a Source of Original Regional Income in Aceh (Case Study in Bireuen Regency, Pidie and Lhokseumawe City) - Syahbandir, Mahdi; Mahfud, Mahfud; Rizki, Muhammad; Wahyu, M. Arizka; Akhyar, M. Nur (Department of Government Studies, Universitas Syiah Kuala, 2023)
Article 21 (2) of Qanun Aceh Number 10, 2007 on Baitul Mal provides that